NOTICES FOR THE DEFINITION ON 2-NORMED SPACE - Malčeski, Aleksa (Matematichki Bilten, 2002)
In this paper is given a review on axioms for 2-normed space. Namely, by help of matrices is given an equivalent definitions for 2-normed spaces from which might be seen than this notion is a thoroughly analogous to the notion of normed space, so the role of the scalar is undertaking by the square matrix from second order.